Leadership Practices in Kindergartens: A Debate Between Capabilities, Importance and Urgency - Galdames-Poblete, S (HIPATIA PRESS, 2024)
Leadership has been identified as one of the most important variables for the success of any educational organization. Previous investigations have focused on the school world, paying less attention to the direction of educational units of preschool education. Considering the recent interest at the international level and in Chile, to develop kindergarten directors as leaders, it is essential to know how the directors understand and implement their role. Inspired by the work of Aubrey et al. (2013) and developed in the context of public gardens managed by the National Board of Kindergartens in Chile, this study seeks to explore the conceptions and practices present in the managerial role. A questionnaire was applied to 86 directors of gardens, inviting them to organize a series of 18 key practices according to three independent dimensions: importance, frequency and capacity. The results show an emphasis on those related to the protection of community rights, a greater capacity to take care of the team and a greater frequency of practices related to establishing direction, evidencing tensions in what is identified as a priority, what they implement and the capacities they perceive to lead. Implications for research, development and policy are discussed.